2005
DOI: 10.1007/s00251-005-0777-3
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic form of a novel chicken ?-defensin identified in silico is predominantly active against intestinal pathogens

Abstract: Antimicrobial peptides are essential components of innate immunity and are generally thought to act by disrupting the membrane integrity of microbes. Here we report the discovery of two novel chicken beta-defensins, gallinacin (Gal)-11 and Gal-12, found by hidden Markov model profile searching of the chicken genome. We have sequenced the genes and elucidated the 3'UTR of Gal-11. Differential mRNA expression of these novel genes has been shown across a panel of chicken tissues. Gal-11 mRNA was highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 46 publications
5
64
0
1
Order By: Relevance
“…Furthermore, we predict that AvBD14 , will be similarly expressed in the tongue, due to the preferential expression of this gene in the head of the embryo and its genomic positioning alongside AvBD3 , AvBD4 , and AvBD5 . In contrast, expression patterns of AvBD8 , AvBD9 and AvBD10 , show localisation of expression to the abdomen of the embryo, correlating with the wider tissue expression panel detected in other studies [42,43] . AvBD11 has an unusual duplicate mature peptide, and therefore to investigate the phylogenetic relationship of this gene, we divided the protein sequence into the propeptide with first mature peptide region (AvBD11a) and the second mature region (AvBD11b).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we predict that AvBD14 , will be similarly expressed in the tongue, due to the preferential expression of this gene in the head of the embryo and its genomic positioning alongside AvBD3 , AvBD4 , and AvBD5 . In contrast, expression patterns of AvBD8 , AvBD9 and AvBD10 , show localisation of expression to the abdomen of the embryo, correlating with the wider tissue expression panel detected in other studies [42,43] . AvBD11 has an unusual duplicate mature peptide, and therefore to investigate the phylogenetic relationship of this gene, we divided the protein sequence into the propeptide with first mature peptide region (AvBD11a) and the second mature region (AvBD11b).…”
Section: Discussionsupporting
confidence: 78%
“…A recent study has shown expression of porcine b-defensin 1 was only present in tongue of newborn piglets, as distinct from a wider panel of tissues in 4-5-week-old pigs [41] . It was therefore o nterest to examine the correlation between this early localisation of b-defensin expression during embryogenesis and the tissue specific expression patterns observed in earlier studies [42,43] . In a similar context, AvBD3 , AvBD4 and AvBD5 have been consistently found to be expressed in the tongue [43][44][45] , which correlates with the localisation of expression of these AvBDs to the head of the embryo in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The significant findings were as follows: (1) the expressions of Gal-1, -2, and -3 in the cells of the vagina increased with age; (2) their expressions were decreased in the regressing oviduct as a result of feed regulation; and (3) Gal-1, -2, and -3 mRNA expression in cultured vaginal cells was enhanced by stimulation with SE and LPS.…”
Section: Discussionmentioning
confidence: 96%
“…Anti-salmonella effect of gallinacins Gal-9, Gal-4, and Gal-7 can be ranked as: Gal-9  Gal-4 > Gal-7 (26), moreover, Gal-7 and Gal-9 have synergistic effect against S. enteriditis. The authors found a notable expression of Gal-11 in the small intestine, liver, gallbladder, and spleen of chickens, Gal-13 was detected in the colon, while other beta-defensins were not identified in the gut (24,27,28). Studying the properties of synthetic Gal-11, it was found to be effective against enteric pathogens including S. typhimurium and Listeria monocytogenes (27).…”
Section: Gut Defenses In Birds (Explanation -See Below)mentioning
confidence: 99%
“…The authors found a notable expression of Gal-11 in the small intestine, liver, gallbladder, and spleen of chickens, Gal-13 was detected in the colon, while other beta-defensins were not identified in the gut (24,27,28). Studying the properties of synthetic Gal-11, it was found to be effective against enteric pathogens including S. typhimurium and Listeria monocytogenes (27). Eight of the 14 recently studied betadefensins of chickens are tissue-specific: AvBD1, AvBD7, and AvBD9 were found in the craw, AvBD8, AvBD10, and AvBD13 -in the gut, AvBD1 and AvBD7 -in the spleen (29).…”
Section: Gut Defenses In Birds (Explanation -See Below)mentioning
confidence: 99%